Vaginal practices among women at risk for HIV acquisition in Soweto, South Africa - Erica Lazarus; Kennedy Otwombe; Janan Dietrich; Michele P. Andrasik; Cecilia A. Morgan; James G. Kublin; Glenda E. Gray; Abby J. Isaacs; Fatima Laher (AOSIS, 2019)
Background: Vaginal practices (VP) may adversely affect normal vaginal flora and mucosal integrity, and increase acquisition risk of HIV and other genital tract infections. Objective: The aim of this study was to describe self-reported VP, changes in the reported number of VP over time and factors associated with VP in a cohort of young Sowetan women enrolled in the HVTN 915 observational study. Method: We longitudinally assessed self-reported VP in 50 young women at risk of HIV acquisition aged 18-25 years in a prospective study over 3 months in Soweto, South Africa. Interviewer-administered HIV behavioural risk questionnaires were completed. No intervention to reduce VP was specified per protocol, but clinicians provided education at their discretion. The generalised estimating equation with inverse probability weights assessed VP over time. Results: The mean age at screening was 22 years; women reported multiple sexual partnerships with a mean of one main and 2 casual partners in the last 30 days. Consistent condom use was 2% (n = 1), 25% (n = 12) and 43% (n = 3) with main, casual and new partners, respectively. Commonly reported VP included washing the vagina with water (44%) and using fingers (48%). VP decreased significantly over time (p < 0.001). Women who used condoms inconsistently or whose last sex was with a casual partner were 3 times more likely to report VP (p = 0.001). Conclusion: Despite the high incidence of HIV in our setting, VP are still common and are associated with other behavioural risks for HIV. Further study is needed to assess whether clinician education may reduce VP and therefore should be included in HIV risk reduction counselling.